Multifunctional zinc ion doped sol – gel derived mesoporous bioactive glass nanoparticles for biomedical applications - Neščáková, Zuzana; Zheng, Kai; Liverani, Liliana; Nawaz, Qaisar; Galusková, Dagmar; Kaňková, Hana; Michálek, Martin; Galusek, Dušan; Boccaccini, Aldo R. (Bioactive Materials, 2019)
Mesoporous bioactive glasses have been widely investigated for applications in bone tissue regeneration and, more recently, in soft tissue repair and wound healing. In this study we produced mesoporous bioactive glass nanoparticles (MBGNs) based on the SiO2–CaO system. With the intention of adding subsidiary biological function, MBGNs were doped with Zn2+ ions. Zn-MBGNs with 8 mol% ZnO content were synthesized via microemulsion assisted sol-gel method. The synthesized particles were homogeneous in shape and size. They exhibited spherical shape, good dispersity, and a size of 130 ± 10 nm. The addition of zinc precursors did not affect the morphology of particles, while their specific surface area increased in comparison to MBGNs. The presence of Zn2+ ions inhibited the formation of hydroxycarbonate apatite (HCAp) on the particles after immersion in simulated body fluid (SBF). No formation of HCAp crystals on the surface of Zn-MBGNs could be observed after 14 days of immersion. Interestingly, powders containing relatively high amount of zinc released Zn2+ ions in low concentration (0.6–1.2 mg L−1) but in a sustained manner. This releasing feature enables Zn-MBGNs to avoid potentially toxic levels of Zn2+ ions, indeed Zn-MBGNs were seen to improve the differentiation of osteoblast-like cells (MG-63). Additionally, Zn-MBGNs showed higher ability to adsorb proteins in comparison to MBGNs, which could indicate a favourable later attachment of cells. Due to their advantageous morphological and physiochemical properties, Zn-MBGNs show great potential as bioactive fillers or drug delivery systems in a variety of applications including bone regeneration and wound healing.
CRIS-Team Scopus Importer:2019-11-01
Keywords: Bioactive glass; Bioactive particles; Bioactivity; Ion release; Sol-gel synthesis; Zinc